PGC-1α Signaling Increases GABA(A) Receptor Subunit α2 Expression, GABAergic Neurotransmission and Anxiety-Like Behavior in Mice - Vanaveski, Taavi; Molchanova, Svetlana; Pham, Dan Duc; Schäfer, Annika; Pajanoja, Ceren; Narvik, Jane; Srinivasan, Vignesh; Urb, Mari; Koivisto, Maria; Vasar, Eero; Timmusk, Tönis; Minkeviciene, Rimante; et al. (Frontiers in Molecular Neuroscience, 2021)
Peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) is a master regulator of mitochondria biogenesis and cell stress playing a role in metabolic and degenerative diseases. In the brain PGC-1α expression has been localized mainly to GABAergic interneurons but its overall role is not fully understood. We observed here that the protein levels of γ-aminobutyric acid (GABA) type A receptor-α2 subunit (GABARα2) were increased in hippocampus and brain cortex in transgenic (Tg) mice overexpressing PGC-1α in neurons. Along with this, GABARα2 expression was enhanced in the hippocampus of the PGC-1α Tg mice, as shown by quantitative PCR. Double immunostainings revealed that GABARα2 co-localized with the synaptic protein gephyrin in higher amounts in the striatum radiatum layer of the hippocampal CA1 region in the Tg compared with Wt mice. Electrophysiology revealed that the frequency of spontaneous and miniature inhibitory postsynaptic currents was increased in the CA1 region in the Tg mice, indicative of an augmented GABAergic transmission. Behavioral tests revealed an increase for anxiety-like behavior in the PGC-1α Tg mice compared with controls. To study whether drugs acting on PPARγ can affect GABARα2, we employed pioglitazone that elevated GABARα2 expression in primary cultured neurons. Similar results were obtained using the specific PPARγ agonist, N-(2-benzoylphenyl)-O-[2-(methyl-2-pyridinylamino) ethyl]-L-tyrosine hydrate (GW1929). These results demonstrate that PGC-1α regulates GABARα2 subunits and GABAergic neurotransmission in the hippocampus with behavioral consequences. This indicates further that drugs like pioglitazone, widely used in the treatment of type 2 diabetes, can influence GABARα2 expression via the PPARγ/PGC-1α system.